Respuesta :

The result function of  (fog)(x) in the given functions is 3x² - 1.

What is the result function of (fog)(x)?

Given the functions in the questions;

  • fx(x) = 3x - 1
  • g(x) = x²
  • (fog)(x) = ?

Set up the composite result function and simplify.

(fog)(x) = f(g(x) = f(x²)

Evaluate f(x²) by substituting in the value of g into f

fx(x) = 3x - 1

f(x²) = 3(x²) - 1

Now, simplify

f(x²) = 3(x²) - 1

f(x²) = 3x² - 1

Therefore the result function of  (fog)(x) in the given functions is 3x² - 1.

Learn more about composite function here: https://brainly.com/question/20379727

#SPJ1